2020
DOI: 10.1139/apnm-2019-0187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 24-h high and low fermentable oligo-, di-, monosaccharide, and polyol diets on markers of exercise-induced gastrointestinal syndrome in response to exertional heat stress

Abstract: The study aimed to determine the effects of 24-h high (HFOD) and low (LFOD) fermentable oligo-, di-, monosaccharide, and polyol (FODMAP) diets before exertional heat stress on gastrointestinal integrity, function, and symptoms. Eighteen endurance runners consumed a HFOD and a LFOD (double-blind crossover design) before completing 2 h of running at 60% maximal oxygen uptake in 35 °C ambient temperature. Blood samples were collected before and after exercise to determine plasma cortisol and intestinal fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(130 citation statements)
references
References 58 publications
5
124
1
Order By: Relevance
“…Participants were provided with a diet low FODMAP diet that met their estimated total daily energy expenditure for the 24-h period before each experimental trial (11.3 ± 1.3 MJ, 440 ± 67 g carbohydrate, 110 ± 8 g protein, 63 ± 8 g fat) to reduce gastrointestinal symptoms arising from pre-exercise food and fluid intake. 18,19 Participants were asked to refrain from consuming additional high-FODMAP foods, alcohol, and caffeinated beverages during the diet-controlled period, and refrained from strenuous exercise during the 48-h period before the experimental trial. Compliance was determined by a dietary and exercise log.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were provided with a diet low FODMAP diet that met their estimated total daily energy expenditure for the 24-h period before each experimental trial (11.3 ± 1.3 MJ, 440 ± 67 g carbohydrate, 110 ± 8 g protein, 63 ± 8 g fat) to reduce gastrointestinal symptoms arising from pre-exercise food and fluid intake. 18,19 Participants were asked to refrain from consuming additional high-FODMAP foods, alcohol, and caffeinated beverages during the diet-controlled period, and refrained from strenuous exercise during the 48-h period before the experimental trial. Compliance was determined by a dietary and exercise log.…”
Section: Methodsmentioning
confidence: 99%
“…Body temperature, measured by rectal thermocouple (12 cm beyond the external anal sphincter; Grant Squirrel data logger, Shepreth, UK), heart rate (short-range radiotelemetry monitor; Polar Electro, Kempele, Finland), rating of perceived exertion (RPE; 6-20 point Likert-type rating scale), 21 thermal comfort rating (13-point Likert-type thermal rating scale, adapted from Hollies & Goldman (1977)), 22 and gastrointestinal symptoms were measured every 10 min during exercise, as previously reported. 4,18,23 Cardiovascular drift (i.e., heart rate variability along steady-state exercise) was established by steady-state exercise heart rate at 120 min minus steady-state exercise heart rate at 10 min. 24,25 Immediately after exercise, blood was collected and nude body mass recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise-induced modulations of the gut microbiota found in this study were strongly associated with favorable changes in several biomarkers of metabolic fitness (e.g., body composition, VO 2max ), suggesting a possible interconnection between exercise stimulus, compositional and functional changes in the gut microbiota that involve hydrogen, and better metabolic health. An earlier study demonstrated that acute exercise augments breath H 2 excretion after lactulose test (Ehrenpreis et al, 2002 ), an outcome corroborated in a recent gut-exercise challenge study (Gaskell et al, 2020 ), implying the colonic bacteria as a source of extra endogenous hydrogen during exercise.…”
mentioning
confidence: 63%
“…When endotoxin is assessed from systemic blood samples, hepatic/immune detoxification might lead to false-negative results, and in exercise settings access to portal blood is rarely feasible. Given the large range in absolute endotoxin concentrations reported between studies (Table 4), several recent attempts have been made to measure MT with alternative biomarkers, though results are equally inconsistent [134,140,165,166]. Thermal stress appears to enhance endotoxin translocation above matched exercise performed in temperate conditions.…”
Section: Severity Of Gi Barrier Integrity Loss Following Exertional-hmentioning
confidence: 99%
“…Currently, little is known about the influence of pre-exercise CHO availability on GI barrier integrity. One study reported that 48-h low (20% CHO, 65% fat) versus high (60% CHO, 25% fat) CHO-diet had no influence on GI MT after a laboratory duathlon [175]; whilst a similar study reported no influence of a 24 h low or high FODMAP diet on GI barrier integrity (I-FABP, LBP, sCD14-ST) following 2 h of exertional-heat stress [166].…”
Section: Carbohydratementioning
confidence: 99%